The Training of Self-Help Eating Ability of the Autism Spectrum Disorder Student using Social Reinforcement Intervention in Early Childhood - Fridolina, Elizabet Petra; Deliana, Sri Maryati; Pranoto, Yuli Kurniawati Sugiyo (Universitas Negeri Semarang, 2020)
The deficit of help-self ability is one of the characteristic of individuals with autism. The impact of low self-help ability can result in delays in the child's growth and development tasks. This research aimed to analyze the effectiveness of social reinforcement towards the self-help eating ability of autism students. The research method used was single subject research with the design A-B-A. The subject on this study was a male autism student in class B of Kindergarten Talenta Semarang. This research was divided into three phases namely baseline A1 (observation) for 5 sessions, intervention B for 8 sessions, social reinforcement intervention given in this phase in the form of verbal praise, soft touch, and so on. The las phase is Baseline A2 which lasts for 4 sessions. The data analysis used was the data analysis inside the condition and among the conditions. To measure the ability of self-help eating autistic students, used 15 performance indicators which include activities before eating, at mealtime, and after eating. The finding of indikator performance in this Baseline A1 phase which obtained the range of data 6- 4,9 , intervention B phase obtained the rage of data 14-11, and the range of data in baseline A2 phase was 11-9. The tendency of the direction from baseline A1 phase to the intervention phase was flat then increased, meanwhile the intervention phase to the baseline A2 was increased then decreased. However the result of the changing of the level in baseline A1 phase to the intervention +5, meanwhile the intervention phase to the baseline A2 -3. Based on that data analysis result, it can be concluded that the treatment of social reinforcement intervention had the long-term effectiveness towards the self-help ability of autism student as long as it is maintained and conducted optimally.